RLS-Based Control Algorithms for 3D Zones of Quiet - MICHALCZYK, Małgorzata I.; SERWIN, Janusz (Archives of Acoustics, 2008)
The paper summarises research on application of RLS-based (recursive least squares)adaptive control algorithms for single-channel active noise control (ANC) system, used tocreate three dimensional (3D) local zones of quiet in a reverberant enclosure by attenuationof tonal disturbances. Three different ANC system structures are concerned: classical“filtered-x”, modified “filtered-x” and “adjoint” structures. A problem of parameterisation ofsix RLS-based adaptive control algorithms is evaluated, initially in simulations with the use of nonsimplified plant models and tonal disturbances. Next, research results are proved in realworldexperiments. Finally, the efficiency of ANC systems using different control structuresand RLS-based control algorithms is compared.